Comparative Analysis of Social Enterprise Regulations in ASEAN: Opportunities for Socio-Economic Development in Indonesia - Artha, Putu Anggi Abelia; Sudharma, Kadek Januarsa Adi; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
Social enterprises have attracted global attention due to their ability to simultaneously combine economic objectives and social missions. Thailand, the Philippines, and Singapore are examples of countries in Southeast Asia that have developed different regulatory frameworks to support the growth of social enterprises. This study aims to analyze the regulation of social enterprises in Thailand, the Philippines, and Singapore and explore relevant and contextual ius constituendum to build a national legal framework for social enterprises in Indonesia. The research method used is a comparative study and literature review of regulations, government policies, and social enterprise development practices in the three countries. The results show that Thailand implements the Social Enterprise Promotion Act that provides legal recognition and fiscal incentives; the Philippines uses a hybrid approach through cooperative regulations and government policies; while Singapore emphasizes ecosystem development through supporting institutions, training, and access to financing. Based on these findings, Indonesia requires a national legal framework that includes formal legal recognition, social and economic accountability, fiscal incentives, and multi-sector collaboration mechanisms, so that social enterprises can play an effective role in sustainable development.